42. Contrasting LMS Marketing Approaches - Carriere, Brain; Challborn, Carl; Moore, James; Nibourg, Theodorus (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The first section of this report examines the CourseCompass learning management system (LMS), made available to educators by the Pearson publishing group as a vehicle for the company’s extensive content library. The product’s features are discussed, and the implications of Pearson’s software/ textbook “bundling” policy for the integrity of course design. The second section of the report reviews Wordcircle, an open source (OS) LMS provided as a free hosted service or as source code downloadable for installation on the user’s own server. The contrasting marketing approaches of these two products are discussed in the light of the increasing move by distance educators from proprietary to open source LMS products. As in previous reports in the series, the reviews are based on the six evaluation criteria of the American Society for Training and Development (ASTD): cost, complexity, control, clarity, common technical framework, and features.